Manajemen Pembaharuan Pembelajaran di Madrasah Ibtidaiyah - Suprihadi Saputro (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
The purpose of this study was to describe the implementation of management of teaching reform in the Islamic Elementary School(Madrasah Ibtidaiyah). This study focused on the process and model of reform management applied in Madrasah Ibtidaiyah Jenderal Sudirman, Malang. A qualitative design was implemented in this study by using a phenomenological approach. Data were analyzed inductively with analysis of domain and taxonomy. It was found out that the teaching reform applied school-based management. The reform was concerning with personnel, infrastructure, school environment, and teaching-learning process. The process of the reform was managed through planning, implementation, evaluation, and institutionalization.